Gel Chemistry Interactions, Structures and Properties - Zhang, Jianyong (Lecture Notes in Chemistry,, 2018)
This book covers various molecular, metal-organic, dynamic covalent, polymer and other gels, focusing on their driving interactions, structures and properties. It consists of six chapters demonstrating interesting examples of these gels, classified by the type of driving interaction, and also discusses the effect of these interactions on the gels' structures and properties. The book offers an interesting and useful guide for a broad readership in various fields of chemical and materials science. .